A Ten Year Retrospective Study of Poisoning Deaths in a Tertiary Care Hospital Situated in Rural Area of Himachal Pradesh - Sharma , S; Arora, V; Saini , T; Parmar, V; Sharma, S; Kumar, D (Journal of Indian Academy of Forensic Medicine, 2023)
Acute poisoning is an important medical emergency and one of the commonest causes of unnatural deaths. Poisoning occurs when any  substance interferes with normal body functions after it is swallowed, inhaled, injected, or absorbed. Toxicology is the science which deals  with the properties, actions, toxicity, fatal dose, detection, estimation, treatment and autopsy findings of poisons, drugs and various  chemical substances. An autopsy based retrospective study was conducted from January 2009 to December 2018 at the Department of  Forensic Medicine and Toxicology, Dr. Rajendra Prasad Government Medical College, Kangra at Tanda, Himachal Pradesh. All cases of  deaths due to alleged poisoning brought for medico-legal autopsy were studied. The data obtained was computed and descriptive analysis  of baseline characteristics was analysed and summarized. In our study, 24.48% of the total cases autopsied were of deaths occurring due to  poisoning. The maximum number of cases 362 (53%) were of males followed by 321(46.99%) cases of females. Aluminium Phosphide  was found to be the most commonly used poison. Peak incidence was observed in the age group 41-50 years (72.34%) in males and 21-30  years (54.27%) in females. Based on these findings preventive measures like restriction of sale and strengthening the legislature on the  availability of poison, promoting poison treatment and detection centres etc. should be the main aim at this time.
Keywords: Pattern of poisoning; Poisoning deaths; Aluminium phosphide; Organophosphates